2006
DOI: 10.1523/jneurosci.3819-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Different Intracellular Pathomechanisms Produce DiverseMyelin Protein ZeroNeuropathies in Transgenic Mice

Abstract: Missense mutations in 22 genes account for one-quarter of Charcot-Marie-Tooth (CMT) hereditary neuropathies. Myelin Protein Zero (MPZ, P0) mutations produce phenotypes ranging from adult demyelinating (CMT1B) to early onset [Déjérine-Sottas syndrome (DSS) or congenital hypomyelination] to predominantly axonal neuropathy, suggesting gain of function mechanisms. To test this directly, we produced mice in which either the MpzS63C (DSS) or MpzS63del (CMT1B) transgene was inserted randomly, so that the endogenous M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
265
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(284 citation statements)
references
References 51 publications
18
265
1
Order By: Relevance
“…At 4 mo, the expression of MpzS63del is lower, similar to endogenous Mpz, (Feltri et al, 1999), even though demyelinating neuropathy becomes more evident in S63del nerves (Wrabetz et al, 2006), similar to patients with MPZS63del, in whom neuropathy appears gradually over the first two decades of life (Miller et al, 2012). Accordingly, transcriptomic analysis showed that the majority of the up-regulated genes were related to inflammation, a typical consequence of demyelinating neuropathy.…”
Section: P0s63del Activates a Robust Stress Response In Transgenic Micementioning
confidence: 76%
See 1 more Smart Citation
“…At 4 mo, the expression of MpzS63del is lower, similar to endogenous Mpz, (Feltri et al, 1999), even though demyelinating neuropathy becomes more evident in S63del nerves (Wrabetz et al, 2006), similar to patients with MPZS63del, in whom neuropathy appears gradually over the first two decades of life (Miller et al, 2012). Accordingly, transcriptomic analysis showed that the majority of the up-regulated genes were related to inflammation, a typical consequence of demyelinating neuropathy.…”
Section: P0s63del Activates a Robust Stress Response In Transgenic Micementioning
confidence: 76%
“…We observed that P0S63del extensively perturbs gene expression following on the expression of the Mpz-based S63del transgene ( Fig. 1 B); in fact, as early as P5, when the transgene is already robustly expressed (Feltri et al, 1999;Wrabetz et al, 2006), 771 genes were found to vary (increased or decreased) by >1.5-fold compared with WT; this number rose to 1,205 genes at P28, when myelination peaks, and decreased to 324 genes at 4 mo, when myelin genes, and thus the MpzS63del transgene, are expressed at lower levels (Wrabetz et al, 2006).…”
mentioning
confidence: 87%
“…S8A) nor in mature nerves (P56, periodicity of mutant vs. wt: 131.7 Ϯ 2.8 Å vs. 132.2 Ϯ 1.6 Å). To accurately measure myelin period and membrane packing, we analyzed the internodal myelin of unfixed late adult mutants by using X-ray diffraction (XRD) (17,18). The relative amount of mutant myelin in sciatic nerve was close to one-half (0.57) of wild-type myelin at P210, due to a reduction in average myelin sheath thickness, whereas no differences were found for the optic nerve (Fig.…”
Section: Scap Deletion Causes a Loss Of Srebp-mediated Gene Expressionmentioning
confidence: 99%
“…However, several mutations cause the mutant protein to be retained in the endoplasmic reticulum (ER) rather than being transported to the cell membrane or myelin sheath. Examples include in vitro studies of MpzSer51delTrp57,2 506delT and 550del3insG3 and in vivo reports of Ser63del and Arg98Cys MPZ mice 4, 5, 6. ER retention in both mouse models activated a canonical unfolded protein response (UPR) 4, 5.…”
Section: Introductionmentioning
confidence: 99%